Communal Crisis and Livelihoods in Akamkpa (A Regression Analysis Study) - Enamhe, Dormcklaims; Tangban, Egbe E.; Omang, Thomas A.; Ojong-Ejoh, Mary U. (SAINSMAT: Journal of Applied Sciences, Mathematics, and Its Education, 2021)
Communal crisis and rural community are juxtaposed given the background that Nigeria is anchored upon a conglomeration of cultures with the assumption that cultural heritage should be enjoyable under a benign condition. Unfortunately, societal dynamics emerged with different value systems and new orientations, paving the way for a "jet age" characterized by deviance, conflict and immediate gratification. Nigerian contemporary society is characterized by an identified crisis with common features of destructive, confrontational and violent dimensions, which has led to the loss of lives and property worth millions of naira. Most rural communities have been characterized by unhealthy conflictual situations, which has eventually turned the settlements into theatres of blood and fire emanating from various communal conflicts. The energy of communal violence has assumed a centre stage in our day-to-day interactions. Despite numerous attempts at stemming the tide of such violence, all concerted efforts have proved abortive. The issue is on the ascendency and has also defied remedial measures to curb such negativing phenomenon. This has a lasting and deleterious effect on the social development of rural communities. Social development means investing in people, which requires the removal of barriers so that all citizens can journey toward their dreams with confidence and dignity. The study adopted a cross-sectional research survey method using a structured questionnaire as an instrument for data collection to examine the impact of the communal crisis on people’s livelihood sources. Data was collected from 800 samples selected from 4 political wards in Akamkpa Local Government Area of Cross River State, Nigeria Descriptive statistics were used to analyze the data. The result from the descriptive analysis was subjected to parametric statistics at 0.05 confidence level. The findings revealed a significant effect of the communal crisis on people’s sources of livelihood in Akamkpa local government area of cross river state, Nigeria. Based on this finding, the study calls for government intervention in the way of policy change and social intervention in the affected area and other parts of Nigeria Affected by communal conflict.